Liquid metal blended micro / nano particle thermal interface material and preparation method thereof
Through ultrasonic blending and in-situ modification technology, carbon nanofibers are uniformly dispersed in liquid metal and blended with diamond particles to form liquid metal/carbon nanofiber/diamond composite materials, which solves the problem that the thermal conductivity is relatively low in the prior art. The problem of this achieves efficient thermal conductivity improvement.
Patent Information
- Application Number
- CN202411572329.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The existing liquid metal-based thermal interface materials have insufficient development in nano-filled particle phases, resulting in low thermal conductivity and difficulty in bonding the interface between carbon nanofibers and liquid metals, affecting the thermal conductivity of composite materials.
Through ultrasonic blending and in-situ modification technology, carbon nanofibers are uniformly dispersed in liquid metal and blended with diamond particles to form liquid metal/carbon nanofiber/diamond composite materials.
The thermal conductivity of the liquid metal blended micro/nanoparticle thermal interface material is significantly improved, and the thermal conductivity in the vertical direction can reach 50-90W/mK, exceeding the thermal conductivity of the liquid metal itself.
Smart Images

Figure CN119432331A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal conductive materials, and in particular relates to a liquid metal blended micro / nanoparticle thermal interface material and a preparation method thereof. Background Art
[0002] With the continuous increase in the power density of electronic devices, the problem of chip heat dissipation has become more and more prominent. The research and application of thermal interface materials can effectively improve the heat dissipation efficiency of chips, reduce their temperature, thereby improving the performance and reliability of chips and extending their service life. However, there are still some problems in the application of thermal interface materials, such as unstable thermal conductivity, insufficient adhesion, and difficult processing. These problems restrict the application and promotion of thermal interface materials. Therefore, how to solve these problems and improve the performance and stability of thermal interface materials is one of the important research directions in the current field of chip heat dissipation.
[0003] Liquid metal-based thermal interface material is a new type of thermal interface material. It has excellent thermal conductivity and good plasticity, so it is widely used in the heat dissipation system of high-power electronic equipment. However, the existing liquid metal-based thermal interface materials are mainly based on micron filling phases, while nano-filling particles are relatively rare. The surface tension of liquid metal (LM) is large, while the surface energy of nano-scale filling particles is high, which makes it difficult to evenly compound the two together, especially for inorganic non-metallic nanofiber materials. The interface between the two is difficult to combine, and the uneven distribution causes the thermal conductivity of the composite material to be low, even lower than the thermal conductivity of the liquid metal itself. Therefore, it is necessary to develop a new technology and adopt new ideas to improve the dispersibility of inorganic non-metallic nanofibers in liquid metals, as well as to significantly enhance the thermal conductivity of new composite materials. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the main purpose of the present invention is to provide a liquid metal blended micro / nanoparticle thermal interface material and a preparation method thereof, by ultrasonically blending and in-situ modifying liquid metal and carbon nanofibers, so that the carbon nanofibers are evenly mixed in the liquid metal, then mixed with diamond, and finally a liquid metal / carbon nanofiber / diamond composite material is obtained by blending. This solves the problem of low thermal conductivity of liquid metal composite nanomaterials in the vertical direction in the prior art.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a liquid metal blended micro / nanoparticle thermal interface material comprises the following steps:
[0007] 1) adding phenolic resin into anhydrous ethanol and stirring to obtain a phenolic resin ethanol solution;
[0008] 2) adding liquid metal and carbon nanofibers into anhydrous ethanol to obtain solution A;
[0009] 3) adding the phenolic resin ethanol solution obtained in step 1) to solution A obtained in step 2) to obtain solution B;
[0010] 4) placing solution B under an ultrasonic crusher for ultrasonic blending and in-situ modification to obtain a suspension;
[0011] 5) vacuum filtering the suspension to remove excess ethanol to obtain a micro-nano mixed sample;
[0012] 6) vacuum drying the micro-nano mixed sample;
[0013] 7) heating and curing the vacuum-dried micro-nano hybrid sample obtained in step 6);
[0014] 8) The micro-nano mixed sample after heating and curing in step 7) is blended with diamond particles to obtain a liquid metal / carbon nanofiber / diamond composite material, namely, a liquid metal blended micro / nanoparticle thermal interface material.
[0015] Furthermore, the mass concentration of the phenolic resin ethanol solution in step 1) is 1%-20%.
[0016] Furthermore, the liquid metal in step 2) is eutectic gallium-indium alloy Ga75In25, or pure gallium.
[0017] Furthermore, in step 2), the mass ratio of the liquid metal to the carbon nanofibers is (99.1-99.9):(0.1-0.9).
[0018] Furthermore, in step 3), the volume ratio of the phenolic resin ethanol solution to the solution A is (2-5):(40-60).
[0019] Furthermore, the process parameters of the ultrasonic blending in step 4) are: blending for 1-10 min at an ultrasonic power of 1000W-1500W.
[0020] Furthermore, the process parameters of the vacuum drying in step 6) are: drying at a temperature of 40° C.-60° C. for 3-5 hours.
[0021] Furthermore, the process parameters of the heating curing in step 7) are: curing at a temperature of 140-180° C. for 10-40 minutes.
[0022] Furthermore, the mass ratio of the diamond particles in step 8) to the solidified micro-nano mixed sample is (30-50):(50-70).
[0023] Liquid metal blended micro / nanoparticle thermal interface material prepared according to the above method.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The present invention relates to a liquid metal blended micro / nanoparticle thermal interface material and a preparation method thereof. The method of the present invention uses a phenolic resin ethanol solution to perform in-situ surface modification on liquid metal and carbon nanofibers, thereby effectively improving the affinity of the interface between the carbon nanofibers and the liquid metal. At the same time, effective interface interconnection is formed under the action of ultrasonic blending to form a complete whole.
[0026] 2. In the liquid metal blended micro / nanoparticle thermal interface material and preparation method thereof of the present invention, the liquid metal and the carbon nanofibers are mixed by ultrasonic blending, so that the carbon nanofibers are evenly dispersed in the liquid metal.
[0027] 3. In the method of the present invention, the liquid metal and carbon nanofibers are ultrasonically blended and in-situ modified to make the carbon nanofibers evenly mixed in the liquid metal to form a complete whole, and then diamond particles are used as the second filling phase to greatly improve the thermal conductivity of the liquid metal blended micro / nanoparticle thermal interface material. The applicant has experimentally verified that the thermal conductivity of the liquid metal blended micro / nanoparticle thermal interface material prepared by the method of the present invention can reach 50-90W / mK in the vertical direction. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0029] Figure 1 This is a process principle diagram of the liquid metal blended micro / nanoparticle thermal interface material provided by the present invention.
[0030] Figure 2 This is a microscopic morphology of liquid metal and carbon nanofibers after ultrasonic blending in Example 1 of the present invention.
[0031] Figure 3 This is a SEM image of the liquid metal blended micro / nanoparticle thermal interface material in Example 1 of the present invention (scale bar is 10 μm).
[0032] Figure 4 This is a SEM image of the liquid metal blended micro / nanoparticle thermal interface material in Example 1 of the present invention (scale bar is 100 μm). DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with the accompanying drawings, the purpose of which is to better understand the content of the present invention rather than to limit the protection scope of the present invention.
[0034] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.
[0035] Sources:
[0036] Carbon nanofiber: Beijing Zhongke Ruijin Technology Co., Ltd.
[0037] Diamond: Zhecheng County Hongxiang Superhard Materials Co., Ltd.
[0038] Liquid Metal: Aladdin
[0039] The present invention relates to a liquid metal blended micro / nanoparticle thermal interface material and a preparation method thereof, the principle diagram of which is as follows Figure 1 shown.
[0040] Example 1
[0041] The preparation method of the liquid metal blended micro / nanoparticle thermal interface material provided by the present invention comprises the following steps:
[0042] 1) Take 2 g of liquid metal eutectic gallium-indium alloy (Ga75In25) and 0.006 g of carbon nanofibers, add them into 60 mL of anhydrous ethanol solution, and simultaneously add 3 mL of 5% phenolic ethanol solution to obtain a mixed sample;
[0043] 2) placing the mixed sample obtained in step 1) under an ultrasonic crusher and ultrasonically blending at a power of 1200 W for 3 min;
[0044] 3) removing the excess ethanol solution in step 2) by suction filtration to obtain a micro-nano mixed sample;
[0045] 4) placing the sample obtained in step 3) in a vacuum drying oven and drying at 40° C. for 3 h;
[0046] 5) Curing the sample in step 4) at 170°C for 30 min;
[0047] 6) Mixing the micro-nano mixed sample after heating and curing in step 5) with diamond (the mass ratio of the micro-nano mixed sample to diamond is 60:40) to obtain a liquid metal blended micro / nano particle thermal interface material. The measured thermal conductivity of the composite material is 82 W / mK.
[0048] The SEM image of the sample after ultrasonic blending of liquid metal and carbon nanofibers prepared in step 1) of this embodiment is shown in Figure 2 ,From the figure, it can be seen that the carbon nanofibers are evenly dispersed among the liquid metal microparticles without obvious ,agglomeration phenomenon.
[0049] The SEM image of the liquid metal blended micro / nanoparticle thermal interface material prepared in this example is shown in Figure 3 , Figure 4 ,in Figure 3 The scale bar is 10 μm. Figure 4 The scale bar is 100 μm. It can be seen from the figure that the diamond particles are interconnected by liquid metal / carbon nanofibers and no obvious phase separation occurs.
[0050] Example 2
[0051] The preparation method of the liquid metal blended micro / nanoparticle thermal interface material provided by the present invention comprises the following steps:
[0052] 1) Take 2 g of liquid metal eutectic gallium-indium alloy (Ga75In25) and 0.012 g of carbon nanofibers, add them to 40 mL of anhydrous ethanol solution, and simultaneously add 2 mL of 10% phenolic ethanol solution to obtain a mixed sample;
[0053] 2) placing the mixed sample of step 1) under an ultrasonic crusher and ultrasonically blending at a power of 1275 W for 3 min;
[0054] 3) removing the excess ethanol solution in step 2) by suction filtration to obtain a micro-nano mixed sample;
[0055] 4) placing the sample obtained in step 3) in a vacuum drying oven and drying at 40° C. for 3 h;
[0056] 5) Curing the sample in step 4) at 180°C for 20 min;
[0057] 6) Mixing the micro-nano hybrid sample after heating and curing in step 5) with diamond (the mass ratio of the micro-nano hybrid sample to diamond is 60:40) to obtain a liquid metal blended micro / nano particle thermal interface material. The measured thermal conductivity of the composite material is 51 W / mK.
[0058] Example 3
[0059] The preparation method of the liquid metal blended micro / nanoparticle thermal interface material provided by the present invention comprises the following steps:
[0060] 1) Take 2 g of liquid metal gallium and 0.013 g of carbon nanofibers, add them to 40 mL of anhydrous ethanol solution, and add 2 mL of 10% phenolic ethanol solution to obtain a mixed sample;
[0061] 2) placing the mixed sample of step 1) under an ultrasonic crusher and ultrasonically blending at a power of 1500 W for 3 min;
[0062] 3) removing the excess ethanol solution in step 2) by suction filtration to obtain a micro-nano mixed sample;
[0063] 4) placing the sample obtained in step 3) in a vacuum drying oven and drying at 40° C. for 3 h;
[0064] 5) Curing the sample in step 4) at 175°C for 25 minutes;
[0065] 6) Mixing the micro / nano hybrid sample after heating and curing in step 5) with diamond (the mass ratio of the micro / nano hybrid sample to diamond is 60:40) to obtain a liquid metal blended micro / nano particle thermal interface material. The measured thermal conductivity of the composite material is 68 W / mK.
[0066] Comparative Example 1
[0067] The preparation method of the liquid metal blended micro / nanoparticle thermal interface material provided by the present invention is basically the same as that of Example 1, except that the carbon nanofiber in step 1) is 0.019 g, specifically:
[0068] 1) Take 2 g of liquid metal eutectic gallium-indium alloy (Ga75In25) and 0.019 g of carbon nanofibers, add them into 60 mL of anhydrous ethanol solution, and add 3 mL of 5% phenolic ethanol solution at the same time;
[0069] 2) placing the mixed sample of step 1) under an ultrasonic crusher and ultrasonically blending at a power of 1200 W for 3 min;
[0070] 3) removing the excess ethanol solution in step 2) by suction filtration to obtain a micro-nano mixed sample;
[0071] 4) placing the sample obtained in step 3) in a vacuum drying oven and drying at 40° C. for 3 h;
[0072] 5) Curing the sample in step 4) at 170°C for 30 min;
[0073] 6) The micro-nano mixed sample after heating and curing in step 5) is mixed with diamond (the mass ratio of the micro-nano mixed sample to diamond is 60:40) to obtain a liquid metal blended micro / nano particle thermal interface material. The measured thermal conductivity of the composite material is 19W / mK; compared with Example 1, it can be seen that the excessive content of carbon nanofibers causes a sharp drop in thermal conductivity.
[0074] Comparative Example 2
[0075] The preparation method of the liquid metal blended micro / nanoparticle thermal interface material provided in this comparative example is basically the same as that of Example 3, except that in step 1), the surface of the carbon nanofibers and the liquid metal is not modified in situ, specifically:
[0076] 1) Take 2 g of liquid metal gallium and 0.013 g of carbon nanofibers, add them into 40 mL of anhydrous ethanol solution to obtain a mixed sample;
[0077] 2) placing the mixed sample of step 1) under an ultrasonic crusher and ultrasonically blending at a power of 1500 W for 3 min;
[0078] 3) removing the excess ethanol solution in step 2) by suction filtration to obtain a micro-nano mixed sample;
[0079] 4) placing the sample obtained in step 3) in a vacuum drying oven and drying at 40° C. for 3 h;
[0080] 5) The micro-nano mixed sample after vacuum drying in step 4) is mixed with diamond (the mass ratio of the micro-nano mixed sample to diamond is 60:40) to obtain a liquid metal blended micro / nano particle thermal interface material. However, the thermal conductivity test cannot be performed because the carbon nanofibers and liquid metal are not in-situ modified by the phenolic ethanol solution, and the carbon nanofibers and liquid metal are in a separated state.
[0081] Comparative Example 3
[0082] The preparation method of the liquid metal blended micro / nanoparticle thermal interface material provided in this comparative example is basically the same as that in Example 3, except that mechanical stirring is used in step 2), and the mechanical stirring is stirring at a stirring speed of 2500 r / min for 45 min, specifically:
[0083] 1) Take 2 g of liquid metal gallium and 0.013 g of carbon nanofibers, add them to 40 mL of anhydrous ethanol solution, and add 2 mL of 10% phenolic ethanol solution to obtain a mixed sample;
[0084] 2) The mixed sample of step 1) was dispersed by mechanical stirring at a stirring speed of 2500 r / min for 45 min;
[0085] 3) removing the excess ethanol solution in step 2) by suction filtration to obtain a micro-nano mixed sample;
[0086] 4) placing the sample obtained in step 3) in a vacuum drying oven and drying at 40° C. for 3 h;
[0087] 5) Curing the sample in step 4) at 175°C for 25 minutes;
[0088] 6) The micro-nano mixed sample after heating and curing in step 5) is mixed with diamond (the mass ratio of the micro-nano mixed sample to diamond is 60:40) to obtain a liquid metal blended micro / nano particle thermal interface material. The thermal conductivity is tested to be 45W / mK. It can be seen that the mixing uniformity of mechanical stirring is much lower than that of ultrasonic stirring.
[0089] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a liquid metal blended micro / nanoparticle thermal interface material, characterized in that: The following steps are involved: 1) adding phenolic resin into anhydrous ethanol and stirring to obtain a phenolic resin ethanol solution; 2) adding liquid metal and carbon nanofibers into anhydrous ethanol to obtain solution A; 3) adding the phenolic resin ethanol solution obtained in step 1) to solution A obtained in step 2) to obtain solution B; 4) placing solution B under an ultrasonic crusher for ultrasonic blending and in-situ modification to obtain a suspension; 5) vacuum filtering the suspension to remove excess ethanol to obtain a micro-nano mixed sample; 6) vacuum drying the micro-nano mixed sample; 7) heating and curing the vacuum-dried micro-nano hybrid sample obtained in step 6); 8) The micro-nano mixed sample after heating and curing in step 7) is blended with diamond particles to obtain a liquid metal / carbon nanofiber / diamond composite material, namely, a liquid metal blended micro / nanoparticle thermal interface material.
2. The preparation method according to claim 1, characterized in that: The mass concentration of the phenolic resin ethanol solution in step 1) is 1%-20%.
3. The preparation method according to claim 2, characterized in that: The liquid metal in step 2) is eutectic gallium-indium alloy Ga75In25, or pure gallium.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the liquid metal to the carbon nanofibers in step 2) is (99.1-99.9):(0.1-0.9).
5. The preparation method according to any one of claims 1 to 4, characterized in that: The volume ratio of the phenolic resin ethanol solution to the solution A in step 3) is (2-5):(40-60).
6. The preparation method according to claim 5, characterized in that: The process parameters of the ultrasonic blending in step 4) are: blending for 1-10 min at an ultrasonic power of 1000W-1500W.
7. The preparation method according to claim 6, characterized in that: The process parameters of vacuum drying in step 6) are: drying at a temperature of 40° C.-60° C. for 3-5 hours.
8. The preparation method according to claim 7, characterized in that: The process parameters of the heating curing in step 7) are: curing at a temperature of 140-180° C. for 10-40 minutes.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The mass ratio of the diamond particles in step 8) to the solidified micro-nano mixed sample is (30-50):(50-70).
10. Liquid metal blended micro / nanoparticle thermal interface material prepared according to any one of claims 1 to 9.